Blast-Resistant Improvement of Sandwich Armor Structure with Aluminum Foam Composite - Shu Yang; Chang Qi (Advances in Materials Science and Engineering)
Sandwich armor structures with aluminum foam can be utilized to protect a military vehicle from harmful blast load such as a landmine explosion. In this paper, a system-level dynamic finite element model is developed to simulate the blast event and to evaluate the blast-resistant performance of the sandwich armor structure. It is found that a sandwich armor structure with only aluminum foam is capable of mitigating crew injuries under a moderate blast load. However, a severe blast load causes force enhancement and results in much worse crew injury. An isolating layer between the aluminum foam and the vehicle floor is introduced to remediate this drawback. The results show that the blast-resistant capability of the innovative sandwich armor structure with the isolating layer increases remarkably.